Potential Theory Lectures given at a Summer School of the Centro Internazionale Matematico Estivo (C.I.M.E.) held in Stresa (Varese), Italy, July 2-10, 1969 - Brelot, M.; Brelot, M. (C.I.M.E. Summer Schools, 2011)
M. Brelot: Historical introduction.- H. Bauer: Harmonic spaces and associated Markov processes.- J.M. Bony: Opérateurs elliptiques dégénérés associés aux axiomatiques de la theorie du potentiel.- J. Deny: Méthodes hilbertiennes en theory du potentiel.- J.L. Doob: Martingale theory – Potential theory.- G. Mokobodzki: Cônes de potentiels et noyaux subordonnés.